2005
DOI: 10.1007/s10457-005-4162-x
|View full text |Cite
|
Sign up to set email alerts
|

Gum arabic yield in differently managed Acacia senegal stands in western Sudan

Abstract: A comparative study of gum arabic yield trends per tree and picking in relation to stand management ͑by farmers and by researchers͒ and type ͑natural and planted͒ was conducted at two locations in North Kordofan, Sudan, for a three-year period. In addition, eight-year yield trends in relation to rainfall were compared based on the 1993-2000 gum yield data from 1440 trees. Although the gum arabic yield followed the same trend over time in all stands at both locations, the gum yield from farm stands, whether pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 7 publications
2
36
0
Order By: Relevance
“…Previous studies of gum yield and quality in provenance trials and natural stands have reported large variation within and among populations in gum yield (Ballal et al 2005;Raddad and Luukkanen 2006a, b;Sprent et al 2010) and quality (Chikamai and Odera 2002;Lelon et al 2010). Both gum yield and quality are complex traits where the biological variability remains poorly understood, but is likely to involve influences of both genetics and environment.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies of gum yield and quality in provenance trials and natural stands have reported large variation within and among populations in gum yield (Ballal et al 2005;Raddad and Luukkanen 2006a, b;Sprent et al 2010) and quality (Chikamai and Odera 2002;Lelon et al 2010). Both gum yield and quality are complex traits where the biological variability remains poorly understood, but is likely to involve influences of both genetics and environment.…”
Section: Introductionmentioning
confidence: 98%
“…The amount of precipitation can also affect other tree secretions such as gum arabic, for which more precipitation immediately prior to the tapping season resulted in a higher yield for Acacia senegal (L.) Willd. trees in western Sudan (Ballal et al, 2005). It is possible that our results showed a negative correlation between resin yield and air temperature owing to the fact that the temperature range was too small to reflect an otherwise potentially positive correlation.…”
Section: Discussion Razpravamentioning
confidence: 70%
“…Considerable variation in gum yield production within and among populations or provenances of A. senegal has been reported in both natural and planted stands. 1,2,9 Apart from environmental factors such as rainfall, temperature and soil type, gum yield can be improved by tapping -deliberate and systematic slashing of the bark from the branches, conducted at the onset of the dry season. Gum arabic is a complex polysaccharide whose quality is defined by biological, physical and chemical parameters, including botanical source, specific optical rotation, intrinsic viscosity, emulsification properties, sugar content, amino acid and mineral content.…”
Section: Gum Source Yield and Qualitymentioning
confidence: 99%
“…In Sudan, new gum producing trees and plantations have continually been recruited from high yielding individuals or populations through natural regeneration, coppicing, direct seeding or transplanted seedlings propagated from local material in rotational bush-fallow agroforestry systems, traditionally known as the gum gardens. 8,9 However, there is no readily available information on how these collections have been deployed, although seed from the gum belt region are now widely used in establishment of trials, new gum plantations or afforestation programmes both within and outside Sudan. …”
Section: Early Selection and Improvement Initiativesmentioning
confidence: 99%